2012
DOI: 10.1002/jbmr.1766
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic processing of osteopontin by PHEX and accumulation of osteopontin fragments in Hyp mouse bone, the murine model of X-linked hypophosphatemia

Abstract: X-linked hypophosphatemia (XLH/HYP)-with renal phosphate wasting, hypophosphatemia, osteomalacia, and tooth abscesses-is caused by mutations in the zinc-metallopeptidase PHEX gene (phosphate-regulating gene with homologies to endopeptidase on the X chromosome). PHEX is highly expressed by mineralized tissue cells. Inactivating mutations in PHEX lead to distal renal effects (implying accumulation of a secreted, circulating phosphaturic factor) and accumulation in bone and teeth of mineralization-inhibiting, aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
111
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(118 citation statements)
references
References 93 publications
5
111
0
Order By: Relevance
“…Our data are consistent with recent comparative evolutionary analyses revealing that Spp1 only emerged together with bone mineralization (Venkatesh et al, 2014), which is under control of preosteocytes, rather than osteoblasts (Dallas and Bonewald, 2010;Franz-Odendaal et al, 2006). Nevertheless, an anti-mineralizing role of Spp1 in (mineralizing) preosteocytes might at first sight be surprising, in particular as its 'partner', the endopeptidase Phex, is known to degrade it (Barros et al, 2013). However, it could be regarded as an intrinsic negative-feedback response, similar to the commonly observed induction of cyp26 expression in response to RA signals (Laue et al, 2008;Loudig et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Our data are consistent with recent comparative evolutionary analyses revealing that Spp1 only emerged together with bone mineralization (Venkatesh et al, 2014), which is under control of preosteocytes, rather than osteoblasts (Dallas and Bonewald, 2010;Franz-Odendaal et al, 2006). Nevertheless, an anti-mineralizing role of Spp1 in (mineralizing) preosteocytes might at first sight be surprising, in particular as its 'partner', the endopeptidase Phex, is known to degrade it (Barros et al, 2013). However, it could be regarded as an intrinsic negative-feedback response, similar to the commonly observed induction of cyp26 expression in response to RA signals (Laue et al, 2008;Loudig et al, 2005).…”
Section: Discussionsupporting
confidence: 91%
“…4A), indicating that this pSer was not phosphorylated by FAM20C. Another study reported several pSers located in non-Ser-X-Glu motifs in BSP (pSer 9 in Ser-Ile-Leu and pSer 18 in SerMet-Lys) (35), which appear unlikely to be phosphorylated by FAM20C. Unfortunately, we were not able to evaluate their phosphorylation status in the KO mice because of the limited MS coverage.…”
Section: Discussionmentioning
confidence: 89%
“…The ASARM peptides in SIBLINGs are believed to inhibit biomineralization through binding to the hydroxyapatite, and an excess of phosphorylated ASARM peptides derived from the overexpressed OPN in Hyp mice is thought to be associated with hypophosphatemic rickets (17)(18)(19). Although the MS analyses in this study did not retrieve the ASARM peptides from OPN, our MS data of BSP derived from Fam20C-KO mice compared with results reported in a previous study of BSP derived from WT mice (3), as well as our MS analyses of DMP1 derived from both WT and Fam20C-KO mice, clearly showed pSer loss in the ASARM motifs in these SIBLINGs (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For other mineralization inhibitors, such as Matrix Extracellular Phosphoglycoprotein (MEPE) and the peptide Acidic Serine and Aspartate-Rich Motif (ASARM) found in SIBLING proteins, the reader can be referred to excellent recent reviews 27,[37][38][39] . 40 …”
Section: General Inhibition Selective Promotion and Selective Inhibimentioning
confidence: 99%